Negara dan Agama Konghucu di Indonesia: Dampak Kebijakan Orde Baru dan Reformasi - Bernadeta Salwa Nirina Kaylasari; Gedong Maulana Kabir; Moch Zulvan Rizaldy Arfiansyah; Patrick Marcelino Luize; Viona Putri Salim (Bina Nusantara University, 2026)
Confucianism is one of the cultural and spiritual heritages of the Chinese community that has long been present in Indonesia. However, throughout its historical development, this religion has faced various challenges, particularly during the New Order era, when the state systematically revoked official recognition of Confucianism and restricted its religious expression as well as Chinese cultural practices. The discrimination experienced by Confucian adherents encompassed administrative, social, and educational dimensions, forcing them to conceal their religious identity and limit their participation in the public sphere. The Reform era marked an important turning point when the government, particularly under President Abdurrahman Wahid, began to restore official recognition of Confucianism and revoke discriminatory policies. Nevertheless, formal recognition alone is insufficient. Sustained commitment from the state is still required to guarantee the right to freedom of religion, eradicate discriminatory practices, and strengthen multicultural education so that diversity in Indonesia is genuinely valued as a national asset. This study aims to analyse the relationship between the state and Confucianism in Indonesia by highlighting the impact of state policies during the New Order and the post-Reform era. The research employs a descriptive qualitative approach, using in-depth interviews to explore the experiences, perceptions, and adaptive strategies of Confucian adherents in responding to state policies. The findings indicate that although the Reform era has opened broader space for recognition and religious freedom, continuous state commitment remains necessary to ensure freedom of religion, eliminate discrimination, and reinforce multicultural education. This study underscores the crucial role of the state in protecting the rights of religious minorities as part of efforts to realize social justice and uphold the values of Pancasila.